Sulfur fixation characteristics of single coal briquette particle during the process of combustion in different atmospheres. (10th October 2020) - Lu, Guangjun; Shen, Qiao; Cheng, Fangqin
Abstract: Fixing sulfur in ash is an important way to reduce SO2 emission from coal combustion. The main purpose of the research is to investigate the transformations of sulfur-bearing minerals and the reaction processes of sulfur fixation in different atmospheres and temperature ranges so as to provide new data for research in sulfur fixation mechanism. As a part of this research, the radial distribution of sulfur fixation products in the combustion process of single coal briquette was studied. It is found that CaSO4 and CaS as sulfur fixation products were formed. CaSO4 distributed in outer layer of coal briquette ash ball, and CaS was in inner layer of ash ball. The results indicated that combustion atmosphere can considerably affect the formation of sulfur fixation products. Furthermore, the main sulfur-containing mineral pyrite (FeS2 ) in coal and CaO were selected to explain the mechanism of sulfur fixation in different atmospheres. The transformations and thermal behaviors of FeS2 and mixture of FeS2 and CaO in oxygen-containing atmosphere and inert atmosphere were studied by means of X-ray diffraction and thermogravimetric analysis. In oxygen-containing atmosphere, FeS2 was decomposed to F1-x S and S2(g) above 390.34 °C, F1-x S was further oxidized to Fe2 O3 and SO2, and then SO2 reacted with CaO and O2 to form CaSO4 . In oxygen-free atmosphere, FeS2 was decomposed to Fe1-x S and S2 (g) above 408.75 °C, CaO reacted with Fe1-x S to form CaS above 847.48 °C. It can be concluded that atmosphere condition affected the sulfur fixation processes, the evolution of sulfur was FeS2 →Fe1-x S→SO2 →CaSO4 in oxygen atmosphere, FeS2 →Fe1-x S→CaS in argon atmosphere in the processes of sulfur fixation. Graphical abstract: Image 1 Highlights: Atmosphere conditions affect the sulfur fixation processes and the sulfur products types. Evolution of sulfur was FeS2 .→Fe1-x S→SO2 →CaSO4 in oxygen atmosphere. Evolution of sulfur was FeS2 .→Fe1-x S→CaS in argon atmosphere. The solid-solid reaction of sulfur fixation occurred in argon atmosphere.